Plant-wide model-based analysis of iron dosage strategies for chemical phosphorus removal in wastewater treatment systems. (15th May 2019) - Kazadi Mbamba, C.; Lindblom, E.; Flores-Alsina, X.; Tait, S.; Anderson, S.; Saagi, R.; Batstone, D.J.; Gernaey, K.V.; Jeppsson, U.
Abstract: Stringent phosphorus discharge standards (i.e. 0.15–0.3 g P.m −3 ) in the Baltic area will compel wastewater treatment practice to augment enhanced biological phosphorus removal (EBPR) with chemical precipitation using metal salts. This study examines control of iron chemical dosing for phosphorus removal under dynamic loading conditions to optimize operational aspects of a membrane biological reactor (MBR) pilot plant. An upgraded version of the Benchmark Simulation Model No. 2 (BSM2) with an improved physico-chemical framework (PCF) is used to develop a plant-wide model for the pilot plant. The PCF consists of an equilibrium approach describing ion speciation and pairing, kinetic minerals precipitation (such as hydrous ferric oxides (HFO) and FePO4 ) as well as adsorption and co-precipitation. Model performance is assessed against data sets from the pilot plant, evaluating the capability to describe water and sludge lines across the treatment process under steady-state operation. Simulated phosphorus differed as little as 5–10% (relative) from measured phosphorus, indicating that the model was representative of reality. The study also shows that environmental factors such as pH, as well operating conditions such as Fe/P molar ratios (1, 1.5 and 2), influence the concentration of dissolved phosphate in the effluent. The time constant of simultaneous precipitation in the calibrated model, due to a step change decrease/increase in FeSO4 dosage, was found to be roughly 5 days, indicating a slow dynamic response due to a multi-step process involving dissolution, oxidation, precipitation, aging, adsorption and co-precipitation. The persistence effect of accumulated iron-precipitates (HFO particulates) in the activated sludge seemed important for phosphorus removal, and therefore solids retention time plays a crucial role according to the model. The aerobic tank was deemed to be the most suitable dosing location for FeSO4 addition, due to high dissolved oxygen levels and good mixing conditions. Finally, dynamic model-based analyses show the benefits of using automatic control when dosing chemicals. Graphical abstract: Image 1 Highlights: A plant-wide model calibrated against extensive pilot-plant data describing phosphorus (P) dynamics with iron (Fe) dosing. Good agreement between measured and modelled P (5–10% (relative) difference). P concentration strongly depends on pH, Fe/P ratio and influent P load. P removal control strategies substantially reduce FeSO4 dose. Model shows aerobic tanks are the most suitable dosing location for FeSO4, due to fast oxidation of Fe 2+ to Fe 3+ .